Drainage Ditch Soil Morphology and Mineralogy Influenced by Hydrologic and Soil Treatments. Issue 4 (9th July 2014) - Ruppert, David E.; Needelman, Brian A.; Rabenhorst, Martin C.; Wester, David B.
Abstract : Drainage ditch soils mediate nutrient and sediment cycling and transport from ditch‐drained agroecosystems. Ditch management may influence the hydromorphology and mineralogy of ditch soils, which in turn may affect their capacity to serve as a nutrient sink. We assessed the effects of hydrologic and soil treatments on ditch soil morphology using mesocosms (15‐cm inner diameter, 20–40 cm length) gathered before and after a dredging event. Hydrologic treatments were continuous saturation, continuous field capacity, and an alternating treatment. Soil treatments were organic soil addition, soil removal, and a control. Mesocosms that experienced continuous saturation developed yellower soil matrices and redox concentrations than other experimental mesocosms; this yellowing was interpreted as a loss of paracrystalline ferrihydrite and a retention of goethite. Iron‐monosulfides and depletions were more abundant in mesocosms experiencing greater degrees of saturation. The loss of ferrihydrite may indicate reduced P sorption capacity. Colluvial or alluvial materials observed in post‐dredged mesocosms indicate the potential of high sediment loss in periods following dredging before vegetation and soil structure establishment.